2013
DOI: 10.1186/1471-2164-14-852
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sea-island cotton and upland cotton in response to Verticillium dahliaeinfection by RNA sequencing

Abstract: BackgroundCotton Verticillium wilt is a serious soil-borne vascular disease that causes great economic loss each year. However, due to the lack of resistant varieties of upland cotton, the molecular mechanisms of resistance to this disease, especially to the pathogen Verticillium dahliae, remain unclear.ResultsWe used the RNA-seq method to research the molecular mechanisms of cotton defence responses to different races of Verticillium dahliae by comparing infected sea-island cotton and upland cotton. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 36 publications
6
66
0
1
Order By: Relevance
“…A 1159 bp unigene containing a NAM domain was obtained through screening differentially expressed genes involved in the cotton defense response to V. dahliae (Sun et al 2013b). The assembled sequence obtained after in silico cloning was the same as the original unigene sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 1159 bp unigene containing a NAM domain was obtained through screening differentially expressed genes involved in the cotton defense response to V. dahliae (Sun et al 2013b). The assembled sequence obtained after in silico cloning was the same as the original unigene sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the previous transcriptome sequencing of sea-island cotton in response to V. dahliae (Sun et al 2013b), we identified the differential expression of a unigene fragment (designated as GbNAC1 ). GbNAC1 encodes a NAC protein with 180 amino acids containing three NAC substructure domains (C–E) (Figure 1A and Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have speculated that a miR482-mediated silencing cascade is involved in the regulation of potato resistance against V. dahliae infection and in the counter defense action of plants in response to pathogen infection [17]. In studies on cotton responses to V. dahliae , Sun et al used the RNA-Seq method to identify 44 differentially expressed genes involved in cotton defense responses [18]. Using the same method, a total of 3027 unigenes were determined as be homologous to known defense-related genes in other plants [19].…”
Section: Introductionmentioning
confidence: 99%
“…qRT-PCR analyses of SiWRKY gene expression in response to waterlogging and drought stresses RNA was extracted from the roots of each of the four cultivars using the EASYspin Plus Plant RNA Kit (Aidlab Biotechnologies, Beijing, China) [60] according to the manufacturer's instructions. The RNA was quantified using a BIOMATE 3 spectrophotometer (Thermo Scientific, Worcester, MA, USA) and its integrity was confirmed using 1% agarose gel electrophoresis.…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%